Explosions of Hydrogen Storages and the Safety Considerations in Hydrogen-Powered Railway Applications—A Review - Yan-Quan Sun (Hydrogen)
As one of the most promising clean energy sources, hydrogen power has gradually emerged as a viable alternative to traditional energy sources. However, hydrogen safety remains a significant concern due to the potential for explosions and the associated risks. This review systematically examines hydrogen explosions, with a focus on high-pressure and low-temperature storage, transportation, and usage processes mostly based on the published papers from 2020. The fundamental principles of hydrogen explosions, classifications, and analysis methods, including experimental testing and numerical simulations, are explored. Key factors influencing hydrogen explosions are also discussed. The safety issues of hydrogen power on railway applications are focused, and finally, recommendations are provided for the safe application of hydrogen power in railway transportation, particularly for long-distance travel and heavy-duty freight trains, with an emphasis on storage safety considerations.